2021
DOI: 10.4102/aosis.2020.bk85.01
|View full text |Cite
|
Sign up to set email alerts
|

Stroke rehabilitation services in Africa – Challenges and opportunities: A scoping review of the literature

Abstract: Collaborative capacity development to complement stroke rehabilitation in AfricaPublished by AOSIS Books, an imprint of AOSIS Publishing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In addition to barriers related to health systems factors, personal factors also substantially impact a stroke survivor’s ability to obtain necessary rehabilitation services. In Zambia and other sub-Saharan Africa settings, adult stroke survivors receive few inpatient and outpatient physical therapy sessions not only as a result of inadequate rehabilitation services but also because of individual challenges, such as insufficient finances, long distances to rehabilitation facilities, and lack of transportation 19 …”
Section: Barriers To Stroke Rehabilitation In Lmicsmentioning
confidence: 99%
“…In addition to barriers related to health systems factors, personal factors also substantially impact a stroke survivor’s ability to obtain necessary rehabilitation services. In Zambia and other sub-Saharan Africa settings, adult stroke survivors receive few inpatient and outpatient physical therapy sessions not only as a result of inadequate rehabilitation services but also because of individual challenges, such as insufficient finances, long distances to rehabilitation facilities, and lack of transportation 19 …”
Section: Barriers To Stroke Rehabilitation In Lmicsmentioning
confidence: 99%
“…Stroke has been and remains a major cause of adult activity limitation and participation restriction, which poses a challenge to the HRQOL among people with stroke (Donkor 2018 ; Gorelick 2019 ; Odetunde, Akinpelu & Odole 2017 ). Stroke prevalence is estimated at 0.5% globally with lower-middle-income countries recording high numbers of stroke deaths and DALYs (4.85m and 91.4m) as compared to high-income countries (1.6m and 21.5m) (Donkor 2018 ; Odetunde, Akinpelu & Odole 2018 ; Shakya et al 2019 ; Tawa et al 2021 ). The global detrimental effects of stroke on activity and participation are the reason why people with stroke seek rehabilitation services to improve symptoms, function and enhance their well-being (Gbiri & Akinpelu 2013 ; Muralidharan et al 2019 ; Winstein et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This, therefore, restricts the utilisation of PROMS in multi-ethnic and multicultural contexts (Odetunde et al 2018 ), like that of Kenya. Global sub-cultural populations are typically defined in terms of lifestyle and dialect and hence the complexity of direct administration of PROMs developed elsewhere in other contexts (Beaton et al 2002 ; Tawa et al 2021 ). Either way, modern healthcare practice is appealing for a global response to cultural adaptation of PROMs to enhance the quality of care post-stroke (Hawkins et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the second most common cause of death [ 3 ], accounts for 102 million disability-adjusted life years (DALYs) globally [ 4 ], and is ranked as the third most common cause of DALYs worldwide [ 5 ]. In Africa specifically, stroke is increasingly “becoming a public health problem...as it causes high rates of disability and mortality” [ 6 ]. Motor-sensory dysfunction that impairs functioning, such as activities of daily living, transfers, and mobility, are concerning sequalae of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Meeting the need for effective and efficient health and rehabilitation services poststroke is imperative to optimize functioning poststroke and to reduce the burden of care [ 7 ]. A recent review found that stroke rehabilitation services in Africa are generally poor, with challenges including “fragmented services, lack of trained personnel, and infrastructure limitations,” which lead to incomplete social and community reintegration of people with stroke in these resource-constrained settings [ 6 ].…”
Section: Introductionmentioning
confidence: 99%